Pengadaan Pelatihan Pembuatan Majalah Sekolah Digital Guna Meningkatkan Minat Baca dan Daya Literasi Siswa di SMKN Jenawi Karanganyar - Sekar Ayu Kartikaning Bonde; Tia Hardiyanti; Sabrina Davina; Meisya Dhevanka Puspaningrum; Ika Anjarsari; Evelyne Henny Lukitasari (LPMP Imperium, 2023)
Reading interest and student literacy are important aspects of education that require attention in Indonesia. Low levels of reading interest and lack of literacy are major problems that need to be addressed. One proposed solution is to utilize digital school magazines to increase students' reading interest and students' literacy skills. This research tried to overcome this problem by organizing training on making digital school magazines at SMKN Jenawi Karanganyar. The training involved students, teachers, and school staff in a series of activities covering various aspects of design, typography, color, photography, the use of CorelDRAW, and the introduction of flipbooks. The results obtained through this study showed that participants managed to understand and apply the material presented with an average success of 84%. The training also successfully increased students' interest in school magazines, with 77% out of 100 students expressing interest in digital school magazines. The digital school magazine